A funcionalidade de crianças com síndrome de down: histórico terapêutico, adaptação parental à deficiência e desempenho ocupacional dos pais - Halberstadt, Bianca Fraga (2019)
The arrival of a child with Down Syndrome (DS) inaugurates several daily changes in the family environment, social and psychological issues, causing frustrations and impacts on the parents, threatening their mental health and well-being. Therefore, the objective of this study is to analyze the functionality of the DS children in relation to mobility, self-care and social function, correlating the effects of the therapeutic history of children, parental adaptation to the disability and occupational performance of the parents. This research is a crosssectional, descriptive, quantitative study. Participants included 30 children aged 10 months to 7 years with DS. Data collection was performed in three municipalities in the interior of Rio Grande do Sul, in institutions responsible for monitoring these children in the public health system. Parents responded to the Pediatric Disability Assessment Inventory (PEDI), the Canadian Measurement of Occupational Performance (COPM), the Parental Adaptation Scale for Child Disability (PASCD), and an interview about the socioeconomic aspects and data on therapy that the child was submitted. The results of the research indicated that the children present better performance in the area of mobility and more delay in the area of selfcare. The socioeconomic and educational level of the parents influences the development of the child in his social functions and in the access of the families to the leisure. The mothers are the primary caregivers of children and families have greater difficulty in dealing with the diagnosis. In contrast, it is easy to see the capacities of the children, especially when the children have better levels of self-care and social function. The occupational problems of the parents are mainly in the area of productivity. The socioeconomic, educational level and the leisure activity of the parents influence the development of the child in his social functions. Families receiving social support have more independent children in self-care. The study concluded that it is necessary for each child and his / her family to have access to the different professions. In order to do so, it is incumbent upon each professional to evaluate and refer the children to the care that will be a priority and will meet the needs of the child and his / her family. The socioeconomic level of the parents and their leisure can be a crucial factor for the development of communication and child socialization, besides providing wellbeing and strengthening of the family bond. Professionals must be attentive to the aspects that permeate the diagnosis and the difficulties in the occupational performance of the parents, acting in a global way to meet the family needs. The support network is crucial for the well-being of families, being associated with higher levels of independence of the child in self-care.